The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1161/strokeaha.108.527705
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Depression After Stroke

Abstract: Background and Purpose— Assessing poststroke depression may be complicated by aphasia, other cognitive deficits, and several somatic stroke-related symptoms. We studied the possible differences in performance of some commonly used instruments in screening depression after stroke. Methods— We compared the Beck Depression Inventory, Hamilton Rating Scale for Depression, Visual Analogue Mood Scale, proxy assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 37 publications
2
52
0
6
Order By: Relevance
“…Williams et al had evaluated the performance of PHQ-9 in assessing post-stroke depression and concluded that PHQ-9 scores discriminate equally well between those with and without PSD regardless of age, gender, or ethnicity and also it was superior to other scales used to assess depression. 7 Demographic variables serve an important role in the development of post-stroke depression. Depressive symptoms were more prevalent among those who were below 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al had evaluated the performance of PHQ-9 in assessing post-stroke depression and concluded that PHQ-9 scores discriminate equally well between those with and without PSD regardless of age, gender, or ethnicity and also it was superior to other scales used to assess depression. 7 Demographic variables serve an important role in the development of post-stroke depression. Depressive symptoms were more prevalent among those who were below 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…This score is in the range originally indicated to characterize mild to moderate depression, 21 but it is up to 4 points above the cutoff for patients with stroke considering similar sensitivity and specificity. 33,34 In the case of the HADS, one review 35 of studies conducted in patients with general medical conditions described optimal cutoff points ranging from 3 to 11 for the depression subscale, with 8 as the cutoff most commonly found; this is also the score originally suggested by the authors of the scale. 22 With regard to TBI, one previous study 9 found a sensitivity of 62% and specificity of 92% for a score of 8 or higher on the HADS, whereas another 11 found a sensitivity of 80% and specificity of 73% for this same cutoff point.…”
Section: Discussionmentioning
confidence: 99%
“…A stroke-ot követő hangulatzavarok gyakoriságára vonatkozó szakirodalmi adatok a PSD defi níciójától, a vizsgált betegcsoporttól, a vizsgálat időpontjától és a vizsgá-latban használt kérdőívektől függően nagyon eltérőek [22,23,24]. A legalacsonyabb érték 1,5%-ban [11], a legmagasabb értéket tartalmazó tanulmány 68%-ban [25] jelöli meg a stroke-ot követő depresszió előfordu-lási gyakoriságát.…”
Section: A Psd Gyakoriságaunclassified
“…A PSD felismerésére önértékelő skálák, illetve interjú formájában kitöltendő kérdőívek állnak rendelkezésre. Az agyérkatasztrófát követő depresszió felismeré-sére megbízhatóan alkalmazhatók a Hamilton Depreszszió Becslő Skála [41], a Beck Depresszió Skála [42], valamint a Montgomery-Asberg Depresszióértékelő Skála (MADRS) [23,43,44].…”
Section: A Psd Szűrése éS Felismeréseunclassified